The Effect of Behavioral Counseling with Self-Management Techniques to Reduce Misbehavior Tendencies in Students: A Gender-Based Analysis - Abdul Aziz, Muhammad; Ni Ketut Suarni; Putu Ari Dharmayanti (Bisma The Journal of Counseling, 2025)
The background of this study is the high level of student misbehavior that disrupts the learning process. The tendency of misbehavior can be overcome with the right counseling approach and technique. Behavioral counseling with self-management techniques. The main objective of the study was to analyze the effect of behavioral counseling with self-management techniques in reducing the tendency of misbehavior, and to explore differences in influence based on gender. The type of research used was an experiment with a "Post-test Only Control Group Design" design. The subjects of the study were 65 grade X students from a total population of 432 students, divided into experimental and control groups. Data were collected through questionnaires, interviews, and observations, with instruments that had been tested for validity and reliability. Data analysis was carried out using two-way analysis of variance (Two Way ANOVA). The results showed a significant effect of behavioral counseling with self-management techniques in reducing the tendency of misbehavior, with an F count of 881.482 and a significance of 0.001. In addition, male students showed a higher level of misbehavior than female students. In conclusion, behavioral counseling with self-management techniques is effective in reducing students' misbehavior tendencies.